2011
DOI: 10.1007/s00405-011-1591-1
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of psychological distress after management of dizziness in old patients: multicenter study

Abstract: Dizziness is a common problem in older people, with a reported prevalence of 13-38%. A large percentage of patients with dizziness develop secondary psychiatric disorders over the course of their disease. In particular, clinical depression and anxiety are significant health problems for older adults. We investigated the relationship between dizziness and psychological distress (depression and anxiety) in elderly patients with dizziness, and the relationship with psychological symptoms after managing the dizzin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 22 publications
(20 reference statements)
0
6
0
1
Order By: Relevance
“…Some authors advocate venlafaxine as first-line therapy for VM for its strong association with psychiatric comorbidities. 25,27,34,35 Interestingly, Salviz et al noted that depressive symptoms alleviated only with venlafaxine when compared to propranolol. 27 Furthermore, venlafaxine also showed better improvement on the emotional scale on DHI.…”
Section: Discussionmentioning
confidence: 99%
“…Some authors advocate venlafaxine as first-line therapy for VM for its strong association with psychiatric comorbidities. 25,27,34,35 Interestingly, Salviz et al noted that depressive symptoms alleviated only with venlafaxine when compared to propranolol. 27 Furthermore, venlafaxine also showed better improvement on the emotional scale on DHI.…”
Section: Discussionmentioning
confidence: 99%
“…However, this may be relevant, as research has revealed that a large percentage of patients presenting with dizziness develop secondary psychiatric disorders over the course of their disease. In particular, clinical depression and anxiety are health problems in older persons [47]. Is dizziness related to depression?…”
Section: Discussionmentioning
confidence: 99%
“…[12] Whether or not the exact reason that caused vertigo complaint has been confirmed, especially in those who have experienced vertigo for prolonged periods, psychologic factors should be expected to accompany the clinical picture. [12] There have been numerous investigations of anxiety and depression in patients with otoneurologic disorders [18][19][20][21][22][23] but health anxiety has not been studied in patients with vestibular complaints. [24] Actually, several features of otoneurologic diseases may be particularly troublesome for patients who are prone to health anxiety.…”
Section: Discussionmentioning
confidence: 99%